2015
DOI: 10.1371/journal.pone.0135352
|View full text |Cite
|
Sign up to set email alerts
|

Key Edaphic Properties Largely Explain Temporal and Geographic Variation in Soil Microbial Communities across Four Biomes

Abstract: Soil microbial communities play a critical role in nutrient transformation and storage in all ecosystems. Quantifying the seasonal and long-term temporal extent of genetic and functional variation of soil microorganisms in response to biotic and abiotic changes within and across ecosystems will inform our understanding of the effect of climate change on these processes. We examined spatial and seasonal variation in microbial communities based on 16S rRNA gene sequencing and phospholipid fatty acid (PLFA) compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 63 publications
8
43
0
Order By: Relevance
“…The pH of unburned soils was more acidic due to organic matter inputs from pine trees, whereas soils from burned forests were more alkaline but also had higher range in pH likely due to differences in burn severity (Figures 2e and 4). Soil pH represents a well-known descriptor of microbial community composition at landscape and biome scales [85][86][87]. Field observations of ash depth, a proxy for burn intensity was positively correlated with pH (r = 0.7, p < 0.05) and patterns of litter depth were also consistent with this interpretation ( Figure A3).…”
Section: Discussionsupporting
confidence: 64%
“…The pH of unburned soils was more acidic due to organic matter inputs from pine trees, whereas soils from burned forests were more alkaline but also had higher range in pH likely due to differences in burn severity (Figures 2e and 4). Soil pH represents a well-known descriptor of microbial community composition at landscape and biome scales [85][86][87]. Field observations of ash depth, a proxy for burn intensity was positively correlated with pH (r = 0.7, p < 0.05) and patterns of litter depth were also consistent with this interpretation ( Figure A3).…”
Section: Discussionsupporting
confidence: 64%
“…pH and vegetation are the main known drivers of worldwide microbial communities, and Arctic microbial communities are no exception. However, other factors may be involved, as studies of worldwide soils have demonstrated the impact of salinity (Lozupone and Knight, ), moisture content (Dimitriu and Grayston, ) and C:N ratio (Docherty et al ., ) on microbial communities. Other factors may include temperature, ice formation/duration, light, altitude, soil age and texture, nutrient and elemental composition, water availability or pollution.…”
Section: Drivers Of Arctic Microbial Communitiesmentioning
confidence: 99%
“…Environmental influence pH. pH has been identified as the main factor driving bacterial diversity in many soil studies (Fierer and Jackson, 2006;Rousk et al, 2010;Griffiths et al, 2011;Chong et al, 2012;Docherty et al, 2015), including in Arctic soils (Chu et al, 2010;Siciliano et al, 2014). Some taxon abundances are closely correlated with soil pH, notably the Acidobacteria (Lauber et al, 2009;Rousk et al, 2010).…”
Section: Drivers Of Arctic Microbial Communitiesmentioning
confidence: 99%
“…This corresponds with higher pH and saturated K in TN and higher soil organic matter and soil moisture in WA. Both pH and water content are major edaphic factors that influence temporal and spatial variation in soil microbial communities (44, 46). Changes in soil physicochemical properties and different climates and soil types between TN and WA could explain such locational differences.…”
Section: Discussionmentioning
confidence: 99%